Mobile Training Unit for Increasing the Quality of Vocational High Schools - Fauriati; Murniati; Ismail (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
The demand to produce graduates with both soft and hard skills is a challenge for vocational high schools to continue innovating. The Mobile Training Unit (MTU) is a program the Aceh government uses to achieve these demands and overcome classic problems in vocational high school teaching, such as a lack of facilities or human resources. This study aims to analyze the Mobile Training Unit for Improving the Quality of Vocational High Schools. This type of research is qualitative with a descriptive approach. The population of this study were three SMKs that had been previously selected together with the MTU program committee. The methods used in collecting data are observation, semi-structured interview guidelines, and documentation. Data collection instrument using a questionnaire. The technique used to analyze the data is a descriptive qualitative analysis using a triangulation process. The research results are that the Mobile Training Unit must be prepared based on the needs of students and mayors in SMK. Determining priorities to become participants, careful preparation and implementation impact improving the quality of SMKs and the motivation of students who need sufficient training. It was concluded that MTU is carried out with careful planning and processes and requires high collaboration and consistency between the government, schools and students.